Candidate attraction and selection methods of companies - Polák, Milan; Legnerová, Kateřina, 1965-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
This thesis focuses on recruitment on entry-level hires, more precisely on the acquisition phase of the recruiting, on attraction and selection part. The paper is divided into two parts: theoretical and analytical. The first aims to provide an overview of attraction and selection procedures. It presents the reader a guide for the start of their recruiting journey in an easy-to-read framework. The second part of the thesis, the analytical part, is the author’s own research. Its main goal is to find out in a sample of CEMS alumni, what attraction and selection methods are most frequently used. Additionally, it surveys them to provide inputs on effort, difficulty, satisfaction, and usefulness of the given method. The results are presented through descriptive statistics. At the end of the thesis, the relationships within variables are researched through linear regression analysis. The end provides conclusion and starting points for further research.
Vedoucí práce: Kateřina Legnerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses